The sort specification of forming wheat winter productivity that depends on sowing terms in the Western region of Ukraine - М. П. Чебаков; Г. Д. Лебедєва; Є. Й. Колач (Plant Varieties Studying and Protection)
Three groups of winter wheat sorts were selected according to their reaction on sowing terms in the Western region of Ukraine. It is shown, that in order to get hight and stable harvests of sorts of intensive type, it is necessary to fit for the terms of sowing with knowing their economic-biological properties and terms of growing.